How Likely is an Economic Depression? - Sarmiento, Camilo (Seventh Sense Research Group (SSRG), 2020)
This paper uses a panel vector-autoregressive (VAR) process with different distributional assumptions to forecast GDP contraction severities and identify the likelihood of a depression threshold event across main Latin American countries. We compare these results to similar hypothetical events for U.S., U.K., France, and Canada.

Este artículo utiliza un proceso de panel vectorial autorregresivo (VAR) con diferentes supuestos distributivos para pronosticar la gravedad de la contracción del PIB e identificar la probabilidad de un evento umbral de depresión en los principales países de América Latina. Comparamos estos resultados con eventos hipotéticos similares para EE. UU., Reino Unido, Francia y Canadá.
Keywords: Crisis económica - América Latina; Depressions - Latin America; Recesiones - América Latina; Recessions - Latin America; Econometría; Econometrics; Economic Depression; Latin America; Tail Event; Vector Autoregressive Model; Depresión Económica; América Latina; Evento de Cola; Modelo Vectorial Autoregresivo